A world shared – a world apart: the experience of families after the death of a significant other late in life. (21st September 2016) - Naef, Rahel; Ward, Richard; Mahrer‐Imhof, Romy; Grande, Gunn
Abstract: Aims: The aim of this study was to investigate the impact of the death of an older member on families. Background: The death of a significant other in later life is a dramatic moment. Research has demonstrated that some older persons face negative consequences for their well‐being. A majority, however, exhibit resilience in the wake of loss. Nonetheless, the relational process through which older persons come to terms with the loss in interaction with their families is little understood, but vital to support bereaved families. Design: Heideggerian hermeneutic phenomenology. Methods: A purposive sample of ten older persons with their families, represented by children, grandchildren and in‐laws ( n = 30) were interviewed several times in 2013, alone ( n = 16) and in family groups ( n = 21), 6‐23 months after their significant other's death (mean age 81 years). Data collection and thematic analysis was informed by van Manen's and Benner's analytical strategies. Findings: Three family themes were discerned. First, through meaning‐making, bereaved families weaved the death into their family narrative. Second, through sharing‐not sharing their feelings and daily moments, family members lived with the loss both together and alone. Third, some families faced upheaval in their family life, which required them to re‐create their everyday life, whereas other families continued with little change. Conclusions: Findings demonstrate that families hold an inherent capacity to make meaning of the death and enact family thereafter. Family relations arose as interplay of different, contradicting forces. Nurses should facilitate families' meaning‐making of the death, attend to their converging and diverging sense of loss and strengthen family caring.